Patient involvement in developing a patient‐targeted feedback intervention after depression screening in primary care within the randomized controlled trial GET.FEEDBACK.GP. (14th April 2020) - Seeralan, Tharanya; Härter, Martin; Koschnitzke, Cornelia; Scholl, Michael; Kohlmann, Sebastian; Lehmann, Marco; Eisele, Marion; Braunschneider, Lea‐Elena; Marx, Gabriella; Scherer, Martin; Löwe, Bernd; Magaard, Julia Luise; et al.
Abstract: Background: Patient and public involvement (PPI) is increasingly required in mental health services research. To empower patients to actively address depression, the GET.FEEDBACK.GP study evaluates a patient‐targeted feedback intervention after depression screening using the Patient Health Questionnaire (PHQ‐9). Objective: To refine the patient‐targeted feedback from a previous study within a participatory research team (PRT) by conducting workshops to investigate patients' needs and preferences for feedback. To evaluate the process and outcome of PPI. Design: Patient and public involvement was carried out on the levels of collaboration and consultation. A PRT of patient partners and researchers planned and conducted three workshops with patients. Patients' needs were investigated using a focus group. Participants prioritized needs, discussed feedback drafts and evaluated two drafts using cognitive debriefings. Researchers of the PRT communicated the results at project level. PPI was evaluated using the Public and Patient Engagement Evaluation Tools (PPEET). Setting and Participants: A purposeful sampling of N = 12 patients with experiences of depression participated in at least one workshop. Results: Relevant content‐related needs about feedback (eg no distinction between severe and moderate symptoms), recommendations for action and patient‐relevant information were considered. Needs for comprehensible, valuing, nonstigmatizing language and design elements (eg dimensional bar) were implemented. Workshops and PRT were positively evaluated. Discussion and Conclusions: Patient and public involvement influenced the content, wording and design of the feedback. Strengths include two levels of PPI, methodical diversity and purposeful sampling. Limitations include the lack of inclusion of patients who are unaware of their depression. The evaluated PPI concept can be useful for future studies.